Politics of Land Law For Indonesian Farmers(Towards the Bill of Land in Indonesia) - Elita Rahmi (International Conference On Law, Business and Governance (ICon-LBG), 2013)
The purpose of this paper are: first, to examine critically how the politics of agrarian law in Indonesia canprovide legal protection for land ownership for farmers in Indonesia, so that the transition of function ofthe land from agricultural land into non-agricultural sector still pays great attention to the farmers as thevulnerable groups (poor, abandoned); second, to examine critically how the draft of the land law whichis now being discussed in parliament can give protection to the farmers, so that they have bargainingposition of land ownership equally with those of the capital owners.This paper uses three analysis namely: 1) juridical analysis to understand the legal norms of the land lawfor the farmers in Indonesia; 2) historical analysis to understand the history of land ownership for farmerssince independence of Indonesia which had not been proporsionil compared with the ownership to thoseof investors in Indonesia; 3) analysis of prospective of agrarian law corcerning with the pros and cons ofthe Bill of Land being discussed before the Parliament.This paper wishes to provide alternative for the rule of land for the farmers, so that the politics of lawrelated to land in Indonesia correlated with farmers’ strategic position as one of the main agents of thedevelopment.